(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2024)
Before I give you some perspective on what it is like to practice forensic pathology in the United States, I would like to give you an idea of my professional background and education. My career as a pathologist extends for 56 years, and as a forensic pathologist/neuropathologist, 50/48 years. I have four boards in pathology: Anatomic Pathology, Clinical Pathology, Forensic Pathology, and Neuropathology. My comments are meant to provide you with a perspective on what some of my colleagues and I have experienced in practicing forensic pathology in the United States.